2019
DOI: 10.1371/journal.pone.0225460
|View full text |Cite
|
Sign up to set email alerts
|

Mortality, morbidity, and cardiac surgery in Injection Drug Use (IDU)-associated versus non-IDU infective endocarditis: The need to expand substance use disorder treatment and harm reduction services

Abstract: BackgroundThe addiction crisis is widespread, and unsafe injection practices among people who inject drugs (PWID) can lead to infective endocarditis.MethodsA retrospective analysis of adult patients with definite or possible infective endocarditis admitted to a tertiary care center in Portland, Maine was performed over three-year period. Our primary objective was to examine differences in demographics, health characteristics, and health service utilization between injection drug use (IDU)-associated infective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 30 publications
2
31
0
Order By: Relevance
“…MOUD has been shown to be associated with reduced rehospitalization but not with mortality after IDU-IE in adjusted analyses. 3 , 9 , 11 , 15 Previous evidence only showed that referral to outpatient addiction treatment was associated with reduced mortality. 4 Therefore, to our knowledge, our finding that mortality was reduced among those actively receiving MOUD after IDU-IE is novel.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MOUD has been shown to be associated with reduced rehospitalization but not with mortality after IDU-IE in adjusted analyses. 3 , 9 , 11 , 15 Previous evidence only showed that referral to outpatient addiction treatment was associated with reduced mortality. 4 Therefore, to our knowledge, our finding that mortality was reduced among those actively receiving MOUD after IDU-IE is novel.…”
Section: Discussionmentioning
confidence: 99%
“…MOUD has been extensively investigated, 10 , 11 , 12 , 13 but data describing the association of MOUD receipt with mortality after IDU-IE–related hospitalization are limited. 3 , 4 , 14 , 15 A national study 9 of privately insured individuals with IDU-IE showed that MOUD was associated with decreased rehospitalizations, but smaller studies 3 , 4 , 14 , 15 investigating mortality have had conflicting results. Studies in Ontario 4 and Boston 14 found no association between MOUD receipt and long-term mortality in patients with IDU-IE; a small study in Maine 15 showed that MOUD was associated with decreased 90-day mortality only in unadjusted analyses.…”
Section: Introductionmentioning
confidence: 99%
“…patients. One possible reason might be that younger IE patients are more often intravenous drug users (IVDU) [27][28][29] and IVDUs' IE admissions have been found to be longer than non-IVDUs' admissions [20,27]. Intravenous drug users' IE is more frequently caused by S. aureus, [11,28] often causing distant foci potentially requiring surgical intervention and consequently longer treatments [30,31].…”
Section: Plos Onementioning
confidence: 99%
“…Although PWID with infective endocarditis tend to be younger and have fewer comorbidities than patients with non–IVDU-associated infective endocarditis, they often have worse outcomes, including higher rates of readmission and mortality. 29 , 30 , 31 , 32 , 33 These disparities are largely due to inadequate treatment of substance use disorders and limited harm reduction services 29 , 30 , 31 , 32 , 33 ; such interventions therefore need to be prioritized for hospitalized PWID.…”
Section: Discussionmentioning
confidence: 99%